Comparison of the Effectiveness of Betel Leaf andBasil Leaf Decoctions on Plaque Index Reductionin Pregnant Women in Pemekaan, Indonesia - Arrozadianti Abadi; Ida Chairanna Mahirawatie; Silvia Prasetyowati; Sunomo Hadi (International Journal of Advanced Health Science and Technology, 2025)
Dental plaque accumulation is a common oral health problem among pregnant women and is associated with anincreased risk of gingivitis, periodontitis, and adverse pregnancy outcomes. In Bunder Village, Pamekasan, preliminaryobservations showed a high plaque index among pregnant women, highlighting the need for accessible and safe plaque-controlinterventions. Natural mouthwash derived from herbal plants such as betel (Piper betle) and basil (Ocimum basilicum) leaves hasbeen suggested to possess antibacterial and antiplaque properties, yet comparative evidence in pregnant populations remainslimited. This study aimed to compare the effectiveness of betel leaf and basil leaf decoctions in reducing dental plaque index amongpregnant women. This quasi-experimental study involved 32 pregnant women selected using Slovin’s formula and randomlyassigned into two equal groups. Each group rinsed with either a boiled betel leaf or basil leaf solution prepared using standardizedprocedures. Plaque index was measured before and after rinsing using the Patient Hygiene Performance (PHP) Index. Datanormality was assessed using the Shapiro–Wilk test, while within-group and between-group differences were analyzed using pairedand independent t-tests, respectively. Both betel and basil leaf decoctions significantly reduced plaque index (p < 0.05). The betel leaf group showed a greater mean reduction (Δ = 1.23 ± 0.75) compared to the basil leaf group (Δ = 0.85 ± 0.65), with the between-group comparison indicating a significant difference favoring betel leaf (p = 0.003). In conclusion, both herbal decoctions effectively lowered plaque index among pregnant women; however, betel leaf decoction demonstrated superior antiplaque efficacy.These findings support the potential use of betel leaf decoction as a low-cost, safe, and natural alternative mouthwash in prenataloral health programs. Further studies with longer follow-up and standardized phytochemical assessment are recommended.